Youth media matters : participatory cultures and literacies in education - Jocson, Korina Mineth (University of Minnesota Press, 2018)
"In an information age of youth social movements, Youth Media Matters examines how young people are using new media technologies to tell stories about themselves and their social worlds. They do so through joint efforts in a range of educational settings and media environments, including high school classrooms, youth media organizations, and social media sites. Korina M. Jocson draws on various theories to show how educators can harness the power of youth media to provide new opportunities for meaningful learning and "do-it-together production." Describing the impact that youth media can have on the broader culture, Jocson demonstrates how it supports expansive literacy practices and promotes civic engagement, particularly among historically marginalized youth. In Youth Media Matters, Jocson offers a connective analysis of content area classrooms, career and technical education, literary and media arts organizations, community television stations, and colleges and universities. She provides examples of youth media work--including videos, television broadcasts, websites, and blogs--produced in the San Francisco Bay Area, Los Angeles, New York, and St. Louis. At a time when educators are increasingly attentive to participatory cultures yet constrained by top-down pedagogical requirements, Jocson highlights the knowledge production and transformative potential of youth media with import both in and out of the classroom"--